If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3w(w + 5) = 0 Reorder the terms: -3w(5 + w) = 0 (5 * -3w + w * -3w) = 0 (-15w + -3w2) = 0 Solving -15w + -3w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '-3w'. -3w(5 + w) = 0 Ignore the factor -3.Subproblem 1
Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0Subproblem 2
Set the factor '(5 + w)' equal to zero and attempt to solve: Simplifying 5 + w = 0 Solving 5 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + w = 0 + -5 Combine like terms: 5 + -5 = 0 0 + w = 0 + -5 w = 0 + -5 Combine like terms: 0 + -5 = -5 w = -5 Simplifying w = -5Solution
w = {0, -5}
| 14*3= | | 4n^2-8=0 | | 5.0n+17.5-4n=13(n-2)19.7 | | 3x^3+15x^2-72x=0 | | -2y^2+4y-2=0 | | -y+3x=2 | | -4q^2+8q-4=0 | | -3n+2=47 | | x^2+23x+53= | | 450,000.00-22,000.00x=-155,000.000+12,000.00x | | 3x^3+15y^2-72x=0 | | -x+3y=2 | | x^6-9y^2= | | 0-2y=12 | | 4(0)-2y=12 | | 4h^2+8h+4=0 | | (b+2)*(b-9)= | | (y-4)*(y+8)= | | 12.5x^3+27y^3= | | 2x-9=43 | | 3(5x+2)=42 | | 3(4x^2+24x-1)= | | -3.7x=-74.0 | | 4s^2+4s-1=0 | | (y+2)*(y-6)= | | X-2x=4 | | 5*22= | | 5x^2+14x=7 | | 2p^2+8p+8=0 | | x^2-30+675=0 | | 24=(14-x)*(10-x) | | -80x^2+8x=0 |